A Daily Diary Investigation of the Defective Self Model Among College Students With Recent Self-Injury. Issue 5 (September 2019) - Lear, Mary K.; Wilkowski, Benjamin M.; Pepper, Carolyn M.
Abstract: The Defective Self Model of self-injury (Hooley, Ho, Slater, & Lockshin, 2010) asserts that individuals choose to self-injure to gratify the desire for self-punishment associated with a self-critical cognitive style. Specifically, self-injury is used to regulate negative self-directed thoughts and emotions and is made accessible via the belief that the individual deserves punishment. This study sought to test primary assumptions of the Defective Self Model using a 2-week daily diary protocol. It was hypothesized that trait self-criticism would predict daily self-injury urge intensity and behaviors directly, as well as indirectly, through daily thoughts about deserving punishment. We also posited that guilt would predict self-injury urge intensity and behaviors beyond sadness, hostility, and fear. Support for primary hypotheses was mixed. Self-criticism did not directly predict self-injury outcomes, but did indirectly predict urge intensity through daily thoughts about punishment. Daily guilt predicted self-injury urge intensity beyond daily sadness, hostility and fear and was the only type of negative affect associated with self-injury behavior. Results are primarily contextualized through a social cognitive lens in which self-injury urge is precipitated by the activation of a self-critical schema in daily life. Alternatively, self-criticism may serve as a gateway to initial self-injury but lack the sensitivity to predict individual self-injury episodes. Treatments designed to reduce self-critical thoughts and bolster self-compassion may decrease self-injury urge intensity, thereby affecting the frequency of self-injury episodes. Highlights: Trait self-criticism did not directly predict self-injury at the daily level. Self-criticism indirectly predicted self-injury urge via daily punishment thoughts. Daily guilt, but not sadness, hostility, or fear predicted self-injury episodes.